Reminders of him : a novel - Hoover, Colleen (Montlake, 2022)
After serving five years in prison for a tragic mistake, Kenna Rowan returns to the town where it all went wrong, hoping to reunite with her four-year-old daughter. But the bridges Kenna burned are proving impossible to rebuild. Everyone in her daughter's life is determined to shut Kenna out, no matter how hard she works to prove herself. The only person who hasn't closed the door on her completely is Ledger Ward, a local bar owner and one of the few remaining links to Kenna's daughter. But if anyone were to discover how Ledger is slowly becoming an important part of Kenna's life, both would risk losing the trust of everyone important to them. The two form a connection despite the pressure surrounding them, but as their romance grows, so does the risk. Kenna must find a way to absolve the mistakes of her past in order to build a future out of hope and healing. --